Design of a zero liquid discharge leachate treatment system using an evapotranspiration willow bed. (1st February 2022) - Frédette, Chloé; Comeau, Yves; Brisson, Jacques
Highlights: ZLD willow bed systems is feasible in humid continental northern climate. Precipitation patterns and type of leachate determine system design and sizing. Water storage volume required is the most limiting aspect of this technology. Closed-circuit and flexibility depend on proper hydraulic management. Optimization options for evapotranspiration include fertilization and bed shape. Abstract: While zero liquid discharge (ZLD) wetlands have been successfully used for domestic wastewater treatment, adapting this technology to treat other wastewaters such as leachate could be very attractive for some industries concerned with meeting increasingly stringent environmental regulations. Leachate treatment typically implies large volume of water that are entirely dependent on rainfall and therefore highly variable both throughout the year and between years. Current design guidelines for zero discharge willow systems limit system flexibility because they are based on rough theoretical estimates of evapotranspiration. This discuss the applicability of ZLD treatment through a willow bed evapotranspiration (ET) applied to the treatment of industrial leachate that has high and variable hydraulic loading rate and low contaminant and salt concentration. We propose a base design and, through detailed and long-term hydrological modeling of such a treatment system, investigate how various design and management decisions can affect sizing, efficiency, and overall feasibility of the technology. We showed that considering ET optimization factors (e.g. fertilization and organic substrate) was essential for ZLD to be achieved over a 20-year period in northern continental humid climate and that the ratio between cumulative annual ET of the willow bed and cumulative annual rainfall should be at least 1.5. When varying the leachate collection area, it was found that a ratio of willow bed area to collection area between 0.5 and 0.7 should be expected for an optimized design in this specific climate, were land area and storage volume remain the most limiting factors. Regarding storage volume, several management options can be applied to reduce the volume of storage required. We also highlight that a risk attenuation strategy should always be included in the design of a ZLD wetland system. Our study suggests that ZLD wetlands constitute a green technology that represents a serious alternative treatment method for pretreated leachate, while offering many benefits such as low maintenance and energy costs, valorization of contaminants such as nitrogen or phosphorus through biomass production, and, most importantly, zero contaminant discharge to the environment. Finally, we propose future research opportunities and other possible applications for further development of the technology. Graphical abstract: Image, graphical abstract